Crizanlizumab in adult patients with sickle cell disease: a retrospective German analysis - Poppenborg, Friederike; Röth, Alexander; Yamamoto, Raina; Reinhardt, Hans Christian; Alashkar, Ferras (Frontiers in Hematology, 2024)
IntroductionThe marketing authorization for crizanlizumab (Adakveo®), indicated for the prevention of recurrent vaso-occlusive crises (VOCs) in sickle cell patients (pts) aged ≥16, was revoked by the European Medicines Agency (EMA) as the STAND study did not demonstrate a significant difference between crizanlizumab and placebo in annualized rates of VOCs.MethodsThis is a retrospective, monocentric analysis of adult pts with sickle cell disease (SCD) (age (median) 29 years, range 19-42, annual VOC rate 3, range 1-5, homozygous SCD (HbS/S) 50.0% (4/8)) receiving crizanlizumab as monotherapy at the University Hospital of Essen between Dec 2020 to May 2023 (observation time (median) 17.5 months, range 4.8-27.3). The results were compared to hydroxycarbamide (HC)-treated pts at maximum tolerated dose (MTD).ResultsAt 6, 9, and 12 months, mean VOC rate was 1.5 (range 0-3; N=6), 1.8 (range 0-3; N=5) and 4.0 (range 3-5; N=3), indicating a time-dependent increase in VOCs in crizanlizumab-treated pts (6-9 months: p=0.039; 6-12 months: p=0.008) (mean VOC rate in HC-treated pts: 6 months: 0.38, range 0-1 (N=8); 9 months: 0.50, range 0-2 (N=8); 12 months: 0.63, range 0-3 (N=8)). Serious adverse events were mandatory in 7 pts, resulting in 12 inpatient-admissions (acute chest syndrome (N=2), VOC-related pain crisis (N=9), infusion-related VOC (N=1)).ConclusionThese findings, together with the high economic burden of crizanlizumab in contrast to HC, do further support the revocation of crizanlizumab in Europe in our opinion. Physicians should consider the potential risks when making a therapeutic decision regarding the use of crizanlizumab outside of Europe.